Analysis and Modeling of Wheel-Based Floating Energy Generation Technology: Analisis dan Pemodelan Teknologi Pembangkit Energi Terapung Berbasis Kincir - Yulikastomo; Dan Mugisidi; Fadhlurrahman Zaki; Oktarina Heriyani (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2024)
This research aims to analyze and model wheel-based floating energy generation technology. The current energy crisis requires us to look for sustainable solutions to meet energy needs. The Indonesian government has targeted renewable energy use of 23% by 2025, especially in remote areas. One solution to overcome this challenge is energy storage technology. Energy storage using floating technology is an innovative solution that is being developed. In this research, we analyze the design of a floating energy wheel with a capacity of 110 kW as an alternative source of electrical energy. Wheel energy is produced from a combination of buoyancy energy and energy originating from the weight of water which is produced by the difference in fluid density in the water and air environments. The research results show that this floating energy wheel can produce a torque of 7710,62 Nm and a power of 113,83 kW, showing great potential in renewable energy storage applications. Wheel-based floating energy generation technology has the potential to be an innovative solution in renewable energy storage. Further research needs to be carried out on a larger scale and field tests to validate the potential and efficiency of this technology in the real world